2014
DOI: 10.18632/oncotarget.2218
|View full text |Cite
|
Sign up to set email alerts
|

Mutational spectrum of adult T-ALL

Abstract: Novel target discovery is warranted to improve treatment in adult T-cell acute lymphoblastic leukemia (T-ALL) patients. We provide a comprehensive study on mutations to enhance the understanding of therapeutic targets and studied 81 adult T-ALL patients. NOTCH1 exhibitedthe highest mutation rate (53%). Mutation frequencies of FBXW7 (10%), WT1 (10%), JAK3 (12%), PHF6 (11%), and BCL11B (10%) were in line with previous reports. We identified recurrent alterations in transcription factors DNM2, and RELN, the WNT p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 65 publications
(96 reference statements)
3
82
1
1
Order By: Relevance
“…In recent years, next-generation sequencing techniques, including whole-genome sequencing, whole-exome sequencing (WES), and RNA sequencing (RNA-seq), have extended the list of genetic abnormalities in T-ALL to epigenetic factors and translation/RNA stability pathways (16)(17)(18)(19)(20)(21). Of note, a subgroup of T-ALL with a characteristic immunophenotype (CD3…”
mentioning
confidence: 99%
“…In recent years, next-generation sequencing techniques, including whole-genome sequencing, whole-exome sequencing (WES), and RNA sequencing (RNA-seq), have extended the list of genetic abnormalities in T-ALL to epigenetic factors and translation/RNA stability pathways (16)(17)(18)(19)(20)(21). Of note, a subgroup of T-ALL with a characteristic immunophenotype (CD3…”
mentioning
confidence: 99%
“…It has been reported that DNM2 gene mutation is an important factor for patients with autosomal dominant centronuclear myopathy (20) and Alzheimer's disease (21,22). Recurrent DNM2 mutations have also been identified in patients with ETP-ALL by whole-exome sequencing (6,10,23). These mutations include: E78fs in the Ras-like GTPase domain; L3354P, R364C, K382E, T404N and E468 * in the dynamin MD domain; S528fs, E544fs and K557_K558>K in the PH domain; S698L in the GTPase effector domain; and K770 * , P791T, L789fs and I805fs in the C-terminus.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, T-ALL was classified into five subgroups (pro-T, pre-T, cortical, mature T-ALL and ETP) based on the results of fluorescent in situ hybridization (FISH), molecular biology and gene expression profiling (4). With exome-sequencing and whole genome sequencing, genetic mutations on genes including NOTCH1, F-box and WD repeat domain containing 7 (FBXW7), Ras, PHD finger protein 6 (PHF6) and Janus kinase 1 (JAK1) have been found to be high-risk markers in patients with T-ALL (3,5,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MLL3 mutation or its deletion is found in hematological malignancies, including 15% of DLBCL, MDS, and AML (Mrozek 2008;Pasqualucci et al 2011;Zhang et al 2013). MLL4 (GeneID 8085) mutations are prevalent in NHL Pasqualucci et al 2011;Lohr et al 2012;Green et al 2015), ALL (Mar et al 2012;Lindqvist et al 2015;Neumann et al 2015), and AML (Kandoth et al 2013). Most of the MLL3 and MLL4/COMPASS mutations are heterozygous nonsense, frameshift, and internal insertions/deletions (indels), resulting in protein truncations-which is suggestive of a haploinsufficient tumor suppressor function of MLL3 and MLL4 (GeneID 8085)-in cancer pathogenesis.…”
Section: Mutations Of Mll3 and Mll4 Members Of The Compass Family In mentioning
confidence: 99%